ANALYSIS OF THE EFFECTIVENESS OF REGIONAL TAXES AND RETRIBUTIONS AND THEIR CONTRIBUTION TO REGIONAL ORIGINAL INCOME IN THE WEST PART OF SERAM DISTRICT - Situmorang, Dokman; Mahadi, Wimbo (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2023)
The aim of this research is to determine the level of effectiveness of regional taxes and levies and their contribution to local original income in West Seram Regency. This research is descriptive qualitative in nature where the object studied is the effectiveness and contribution of regional tax revenues and their contribution to local original income in West Seram Regency. The research was carried out by means of descriptive comparative analysis. The results of the analysis show that the level of effectiveness of Regional Taxes and Regional Levies in West Seram Regency is effective for Regional Taxes and not effective for Regional Levies. In addition, the contribution of Regional Taxes and Levies to the Original Regional Income of West Seram Regency for the 2015 to Fiscal Year. 2019 is categorized as moderate for Regional Taxes, and very low for Regional Levies. This condition is caused by the lack of effectiveness in collecting regional taxes and levies carried out by the West Seram Regency Government. Apart from that, the implementation of revenue targets is still small and inconsistent from year to year.